Apelin‐13 and APJ in paraventricular nucleus contribute to hypertension via sympathetic activation and vasopressin release in spontaneously hypertensive rats. (18th July 2014) - Zhang, F.; Sun, H.‐J.; Xiong, X.‐Q.; Chen, Q.; Li, Y.‐H.; Kang, Y.‐M.; Wang, J.‐J.; Gao, X.‐Y.; Zhu, G.‐Q.
Abstract Aims Apelin is a specific endogenous ligand of orphan G protein‐coupled receptor APJ. This study was designed to determine the roles and mechanisms of apelin‐13 and APJ in paraventricular nucleus (PVN) in renal sympathetic nerve activity (RSNA), arginine vasopressin (AVP) release and mean arterial pressure (MAP) in spontaneously hypertensive rats (SHR). Method Acute experiment was carried out in 13‐week‐old male SHR and Wistar‐Kyoto rats (WKY) under anaesthesia. RSNA and MAP responses to the PVN microinjection were determined. Apelin and APJ expressions were examined with quantitative real‐time PCR and Western blot. AVP and noradrenaline were determined with ELISA. Osmotic minipumps were used for chronic PVN infusion in conscious WKY. Results Apelin and APJ in the PVN were up‐regulated in SHR. The PVN microinjection of apelin‐13 increased, but APJ antagonist F13A decreased the RSNA, MAP, plasma noradrenaline and AVP levels in SHR. N‐methyl‐D‐aspartate receptor (NMDAR) antagonist plus non‐NMDAR antagonist abolished the apelin‐13‐induced sympathetic activation rather than AVP release. NMDAR antagonist or non‐NMDAR antagonist alone attenuated the apelin‐13‐induced sympathetic activation. Chronic infusion of apelin‐13 into the PVN in normotensive rats induced hypertension, increased plasma noradrenaline and AVP levels and promoted myocardial atrial natriuretic peptide and beta‐myosin heavy chain mRNA expressions, two indicative markers of cardiac hypertrophy. Conclusion Apelin‐13 and APJ in the PVN contribute to hypertension via sympathetic activation and AVP release in SHR. The sympatho‐excitatory effect of apeline‐13 is mediated by both NMDAR and non‐NMDAR in the PVN. Persistent activation of APJ in the PVN induces hypertension.